Perubahan Bilangan Peroksida pada Blending VCO-Ekstrak Likopen Buah Tomat Berdasarkan Perbandingan Rasio dan Lama Penyimpanan: Peroxide Value Changes on Blending of VCO and Extract of Tomato Lycopene Based on Ratio Comparison and Storage Time - Muqasyifah; Nurhaeni; Syamsuddin; Khairuddin (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
Utilizing of lycopene extract in VCO has serve as antioxidant agent that protected VCO from oxidation process during storage. Belnding of VCO and tomato lycopene extract has been done that purpose to determine changes in peroxide number in the mixture of VCO-lycopene extract tomatoes based on comparison of ratios and length of storage. Peroxide contents from the mixture of tomato extract with VCO were determined using a spectrophotometric method at a wavelength of 500 nm. The results showed that the best results were obtained at a ratio of 40: 3 (v/w) with peroxide numbers 0.08 meq O2/ kg, 1.38 meq O2/ kg, 1.84 meq O2/ kg, 3.21 meq O2/ kg, 3.46 meq O2/ kg and 3.83 meq O2/ kg respectively. Peroxide numbers increased with increasing storage time, the highest increase occurred at week 3 at a ratio of 40: 1 (v/w) which was equal to 9.62 meq O2/ kg. The addition of lycopene was better at reducing the VCO oxidation process than without the addition of lycopene. Keywords: peroxide value, VCO, lycopene, duration of storage, ratio comparison